The state, development, and identity in multi-ethnic societies [ ethnicity, equity, and the nation - Gomez, Edmund Terence; Tarling, Nicholas (London ; New York : Routledge, 2008)
This book examines ethnic communities, identity, economy, society and state, and the links between them, in a range of countries across Asia, challenging the widely held belief that an authoritarian political system is necessary to ensure communal co-existence in developing countries where ethnic minorities have a considerable economic presence.
1. Introduction: Modernization, democracy, equity and identity -- 2. Ethnicity -- 3. Inter-ethnic relations, business and identity: The Chinese in Britain and Malaysia -- 4. Beyond reductionism: State, ethnicity and public policy in plural societies -- 5. Ethnic identity formation: The case of second generation Chinese and Vietnamese in the United States -- 6. A world on fire?: Some notes on Burma -- 7. Hidden in plain view: Singapore's race and ethnicity policies
Description based on print version record
Includes bibliographical references and index
Keywords: Ethnicity -- Asia; Minorities -- Asia